Preeclampsia and COVID-19: results from the INTERCOVID prospective longitudinal study - Papageorghiou, AT; Villar, J; Deruelle, P; Gunier, RB; Rauch, S; García-May, PK; Mhatre, M; Usman, MA; Abd-Elsalam, S; Etuk, S; Simmons, LE; Napolitano, R; et al. (Elsevier, 2021)
Background: It is unclear whether the suggested link between COVID-19 during pregnancy and preeclampsia is an independent association or if these are caused by common risk factors.